Perspectives of New Alternative Materials to Silicon for the Production of Photovoltaic Solar Cells: A Systematic Literature Review - Teixeira, Marco Antonio Casadei; Ramos, Heidy Rodriguez; Aguiar, Alexandre de Oliveira e (Revista Nacional de Gerenciamento de Cidades, 2021)
Much has been studied about solar energy as a renewable energy, as it can be transformed in electricity by means of solar panels. Innovation is very important when it comes to photovoltaic technologies, because the advantages of these technologies are low installation and maintenance costs and no environmental impact during operation. The market of photovoltaic products is dominated by the silicon technology, but new second- and third-generation cell technologies have been developed. This research shows that the Perovskite solar and the Multijunction solar cells have the potential to achieve maximum power conversion efficiency and minimum production costs in the near future. Dye-sensitized solar cells (DSSC), Organic photovoltaics (OPV), Quantum dot sensitized solar cells (QDSSC), Single-junction solar cells, and the Heterojunction solar cells will achieve such potential in a more distant future, because limitations imposed by efficiency and costs must be overcome. Having these parameters in mind, the overall objective of this research is to analyze the materials of strategic potential to compete with silicon in the composition of the photovoltaic solar cells. A Systematic Literature Review helped retrieve 112 papers that report the most researched materials from 2014 to 2018. It is concluded that despite good results have been obtained from many of such studies, some alternative materials to silicon are still not technologically acceptable in terms of efficiency. It is expected that the use of a better distributed and cheaper solar energy technology will be possible in the near future.